"Research Jam": Engaging patients and other stakeholders through human-centered design to improve translational research. Issue 1 (14th November 2023) - Wiehe, Sarah E.; Moore, Courtney M.; Lynch, Dustin O.; Claxton, Gina; Bauer, Nerissa S.; Sanematsu, Helen
Abstract: Effective stakeholder engagement increases research relevance and utility. Though published principles of community-based participatory research and patient-centered outcomes research offer guidance, few resources offer effective techniques to engage stakeholders and translate their engagement into improvements in research process and outcomes. The Indiana Clinical and Translational Sciences Institute (Indiana CTSI) is home to Research Jam (RJ), an interdisciplinary team of researchers, project management professionals, and design experts, that employs human-centered design (HCD) to engage stakeholders in the research process. Establishing HCD services at the Indiana CTSI has allowed for accessible and innovative stakeholder-engaged research. RJ offers services for stakeholder-informed study design, measurement, implementation, and dissemination. RJ's services are in demand to address research barriers pertaining to a diverse array of health topics and stakeholder groups. As a result, the RJ team has grown significantly with both institutional and extramural support. Researchers involved in RJ projects report that working with RJ helped them learn how to better engage with stakeholders in research and changed the way they approach working with stakeholders. RJ can serve as a potential model for effectively engaging stakeholders through HCD to improve translational research.